Improving the Ability to Design Instruction Activities through Anderson-Krathwohl Taxonomy: CBPR Research among PGMI Students and Alumni - Khairunnisa, Khairunnisa; Jannah, Raihanatul (Institut Agama Islam Negeri Palangka Raya, 2024)
Well-planned instructional activities are essential for achieving effective learning objectives. This work presents participants’ understanding of Anderson and Krathwohl’s Taxonomy (AKT) and its implementation in designing learning activities using a structured framework for teaching. The community service project involved 20 participants, comprising students and alumni of PGMI at UIN Antasari and UNISKA Banjarmasin. A Community-Based Participatory Research (CBPR) approach was used, including material delivery, technical assistance, and lesson planning simulation based on AKT. Pretest results showed a low average score of 52.3, which increased to 73.2 in the post-test (high category), with an N-Gain score of 0.44 (medium improvement). All participants successfully designed learning paths based on the AKT table, aligning cognitive processes with knowledge dimensions. These results suggest that AKT understanding improves the ability to develop structured lesson plans that support the achievement of higher-order thinking skills (HOTS).